Amistad - Dreamworks Pictures; HBO Pictures ([Universal City, Calif.] DreamWorks, 1997)
Chronicles the 1839 revolt on board a slave ship bound for America. Much of the story involves the court-room drama about the slave who led the revolt.
The producers want to acknowledge the book "Black mutiny : the revolt on the schooner Amistad" by William A. Owens as the major source of reference materials.
Directed by Steven Spielberg ; written by David Franzoni ; produced by Steven Spielberg, Debbie Allen, Colin Wilson.
Morgan Freeman, Nigel Hawthorne, Anthony Hopkins, Djimon Hounsou, Matthew McConaughey.
Keywords: Amistad (Schooner); Feature films; Slave insurrections -- United States